Weighted Badly Approximable Vectors and Games. (7th July 2017) - Guan, Lifan; Yu, Jun
Abstract: Let d2 . We show that the set Bad(r) of r -badly approximable vectors in R^d is hyperplane absolute winning, hence is 1/2 -winning for certain one-dimensional family of weights r .